THE EFFECT OF PRODUCT QUALITY, PRICE, AND PROMOTION ON PURCHASING DECISIONS AT KOPI JANJI JIWA IN MAKASSAR - Gabriele Gonardy; Klara Felicia Jonardi; Jennifer Wityono; Richard Laurenta; Bryan Maxwell Jong Ganing; Muh Syulhasbiullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Purchasing decisions are inherent in every customer’s behavior. The purpose of this study is to analyze the influence of product quality, price, and promotion on purchasing decisions at Kopi Janji Jiwa in Makassar. The research data were collected through the distribution of closed-ended questionnaires using a Likert scale. The analytical tools employed in this study include descriptive statistical analysis, data quality tests (validity and reliability tests), hypothesis testing, multiple linear regression, and classical assumption tests using SPSS version 26. The results indicate that product quality (X1) has no significant effect on purchasing decisions (Y), price (X2) also has no significant effect on purchasing decisions (Y), while promotion (X3) has a significant influence on purchasing decisions. It can be concluded that simultaneously, product quality, price, and promotion collectively affect purchasing decisions.